2020
DOI: 10.1002/slct.202003233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vesicle Structure on Catalytic Activity of Suzuki‐Miyaura Cross‐Coupling Reaction: Impact of Framework and Morphology

Abstract: A novel hybrid porous polymer with hollow vesicle structure has been synthesized via Friedel-Crafts alkylation reaction and solvent-induced method. The resulting two-dimensional networks are hierarchical porous materials with high Brunauer-Emmett-Teller (BET) surface area of 1582 m 2 g À 1. The vesicle structure directly influenced the activity and shaping the performance of the catalyst. The kinetic study reveals the special vesicle structure can enrich the substrates in a limit scope and increase the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In 2020, Zhou et al reported a novel catalyst with a hollow vesicle structure, where they found that the vesicle structure directly influenced the activity and performance of the catalyst [ 101 ]. Kinetic studies indicated that the unique vesicle structure allowed for substrate enrichment within a confined range, leading to an enhanced reaction rate.…”
Section: The Effects Of Pore Size Modulation and Shape Tailoring Of H...mentioning
confidence: 99%
“…In 2020, Zhou et al reported a novel catalyst with a hollow vesicle structure, where they found that the vesicle structure directly influenced the activity and performance of the catalyst [ 101 ]. Kinetic studies indicated that the unique vesicle structure allowed for substrate enrichment within a confined range, leading to an enhanced reaction rate.…”
Section: The Effects Of Pore Size Modulation and Shape Tailoring Of H...mentioning
confidence: 99%